Gastrointestinal symptoms and sleep disturbance in female nurses - Samara, Diana (Universa Medicina, 2009)
Sleep disturbance is a common symptom in the general population. An association between sleep disturbances and functional gastrointestinal (GI) disorders has been reported by several investigators. GI symptoms are more common among people with sleep disturbance in female nurses. To explore this issue further, a study using a cross sectional design was conducted to determine whether unexplained GI symptoms are more common in female nurses with self-reported sleep disturbance. This study was conducted from February through April 2007 in Hospital X in Central Jakarta. A total of 152 female nurses participated in this study. A questionnaire consisting mainly of items concerning sleep disturbance was distributed to the subjects. Significant associations were observed between gastrointestinal symptoms such as anorexia and constipation and sleep disturbance. Constipation was significantly more common in female nurses with sleep disturbance (prevalence ratio=6.1;95% C.I. 1.76 â 20.56), but the association between shift work and sleep disturbance was not statistically significant (prevalence ratio=1.67;95% C.I. 0.53-5.24). Both constipation and anorexia are more prevalent in female nurses with self-reported sleep disturbance. Further research to understand the associations between GI symptoms and sleep disturbance is warranted.